FERONIA-like receptor 1-mediated calcium ion homeostasis is involved in the immune response - Luo, Xiao; Wang, Long; Fu, Yuefeng; Liu, Qiqi; Chen, Ge; Liu, Yue; He, Wei; Gao, Aijun; Xu, Jingbo; Deng, Huafeng; Xing, Junjie (Frontiers in Plant Science, 2022)
Calcium (Ca2+) is the most abundant divalent cation in plants, and cellular levels of Ca2+, which functions as a nutrient and secondary messenger, play a critical role in plant immunity. In the present study, we found that FERONIA-like receptor 1 (FLR1) positively regulates Magnaporthe oryzae resistance and that expression of FLR1 is strongly induced in response to Ca2+ deficiency. In addition, the Ca content in the shoots of flr1 was lower than that in wild-type, and the M. oryzae-sensitive phenotype of the flr1 mutant was not rescued by exogenous application of Ca2+. Moreover, RNA sequencing revealed 2,697 differentially expressed genes (DEGs) in the flr1 mutant compared with wild-type, and some of these DEGs are involved in cellular metal ion homeostasis and transition metal ion homeostasis. Changes in expression of overlapping genes between the flr1 mutant and in plants under low-Ca2+ treatment were consistent in terms of direction, indicating that FLR1 is involved in Ca2+ homeostasis. In summary, we detected FLR1-mediated resistance to M. oryzae, a phenomenon associated with Ca2+ homeostasis.